Új kihívások egy kisváros interregionális kapcsolataiban a magyar-román határszélen : létavértesi esettanulmány - Baranyi, Béla (Közép-Európai Közlemények, 2013)
Following the Treaty of Trianon (1920), Létavértes –similarly to several other Hungarian settlements –suddenly became a severely disadvantaged region locked out of its original catchment area along the Hungarian-Romanian border on the outer (cross-border) periphery. The new border totally ignored the inter-settlement catchment relations which developed during the history and all traffic-related, economic, infrastructural, cultural and inter-ethnic or even geographical aspects, while it caused a severe breach in the life of the settlements on both sides of the border. It became the most severe and still problematic consequence of the Treaty of Trianon that it shattered the multilateral system of relations which connected Létavértes to the larger cities on the other side of the border. The economic and social development of the dynamically developing Nagyléta slowed down which could not be prevented by the fact that instead of the former district centre Székelyhíd (which was annexed to Romania), Nagyléta, a town stuck in the broken Bihar county, played an important public administrative role between 1920 and 1955 as a district centre. Ever since, the settlements along the border still have increasingly strong relations with Létavértes from social and economic aspects. The town became a key settlement and its developed service provider network enables Létavértes to play a significant role in helping the surrounding villages, especially since the union of Vértes and Nagyléta in 1970 and its city ranking which was given to Létavértes in 1996. In the new situation resulting as a positive consequence of the Schengen process, the study (in the form of a case study) focuses on the possible content and form of the rebuilding of interregional relations in the internal border of the Schengen area since it is less restricted by country borders.